ON PRIME AND MAXIMAL k-SUBSEMIMODULES OF SEMIMODULES - Yesilot, Gursel (HACETTEPE UNIV, FAC SCI, 2010)
In this paper, we present some characterizations of prime k-ideals and maximal k-ideals of a semiring. Then we extend these properties to prime k-subsemimodules and maximal k-subsemimodules of a semimodule. After that, the correspondence between prime k-ideals and prime k-subsemimodules, and between maximal k-ideals and maximal k-subsemimodules are given.
Keywords: Prime k-ideal; Maximal k-ideal; Prime k-subsemimodule; Maximal k-subsemimodule; SEMIRINGS; Mathematics